Myths and unhealthy wound practices regarding animal bite among subjects attending anti rabies clinic in a South Delhi municipal corporation polyclinic in Mehrauli, Delhi - Arora, Shweta; Ray, T. K.; Gupta, Ekta; Joseph, Blessy; K., Arunraj; Rasania, S. K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Rabies is one of the highly fatal diseases, with nearly fifty nine thousand deaths annually globally and almost one third of these are in India. Higher rates of dog bites are common in our country, due to large stray dog population. Despite a preventable disease, unhealthy wound practices are still prevailing in the community due to lot of myths related to the disease. The objectives of the study were to assess the magnitude of unhealthy wound practices and to assess the knowledge regarding health seeking behaviour following animal bite. Methods: The present study was a cross sectional study conducted at SDMC Polyclinic, Mehrauli, Delhi from January to December 2015. A total of 160 cases of animal bite that attended OPD and consented were analysed for knowledge, practices and health seeking behaviour towards animal bite. Results: Out of total 160 respondents almost all were bitten by dogs of which 2/3rd was stray dogs and most common site of bite was lower limb. 55% of the subjects did not wash or clean the wounds after bite. 27% of subjects applied chilli powder or its paste with oil and 2.5% used oil and turmeric paste and 1.9% oil on the wound. Only 41.9% of the subjects believed that vaccination is the treatment of the choice following animal bite. Conclusions: Intensive health education through mass media and mid media can be used to create awareness about the disease transmission and preventive measures like wound management and post-exposure prophylaxis. Also, pet vaccination should be made mandatory for all those who keep pets.